Innovation Performance and its Influence on Enterprise Economic Efficiency in the Market - Prokhorova, Maria P.; Prodanova, Natalia A.; Reznichenko, Sergey M.; Vasiliev, Vyacheslav P.; Kireev, Vasiliy S. (International Journal of Economics and Financial Issues, 2016)
Innovations are means of competition. A success in how an enterprise uses the innovation processes directly depends on its competitive ability and profitability level. Innovation performance is a level of using innovations. Under a competitive struggle in the market, progress in science and technology holds a specific place. Innovations define the economic success of an organization. It is not simple to have only a desire to increase the performance results, it is necessary to have a factor for organization survival, competitive ability and economic growth prospects preservation throughout the modern innovation world. The experience of the most developed countries shows that the one, whose activity is mainly based on using the innovation processes, becomes a winner in a fight for his client and the main purpose of organizations' strategic plan is to develop either a new product or services. The innovation performance of an enterprise can become one of the main factors for organizing the competitive strategic prospects of an enterprise, preserving and increasing its positions in the market. The topicality of the theme is very high, as introducing innovations in the activity of an enterprise and its competitive ability level in the market depend on the level of an organization's innovation performance. Keywords: innovation, innovation performance JEL Classifications: O14, O31, O32, O33